The Wiley encyclopedia of packaging technology - Yam, Kit L. (John Wiley & Sons, 2009)
* Provides information on every stage of the packaging process and extensive bibliography, written by renowned experts from around the world * Based on the content and format of previous editions with additions, revisions, and modernization of the content reflecting changes and developments in the field over the past decade.